2015
DOI: 10.1063/1.4908287
|View full text |Cite
|
Sign up to set email alerts
|

Proximity induced vortices and long-range triplet supercurrents in ferromagnetic Josephson junctions and spin valves

Abstract: Using a spin-parameterized quasiclassical Keldysh-Usadel technique, we theoretically study supercurrent transport in several types of diffusive ferromagnetic(F )/superconducting(S) configurations with differing magnetization textures. We separate out the even-and odd-frequency components of the supercurrent within the low proximity limit and identify the relative contributions from the singlet and triplet channels. We first consider inhomogeneous one-dimensional Josephson structures consisting of a uniform bil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 104 publications
(258 reference statements)
1
54
0
Order By: Relevance
“…Two-dimensional vortex lattices are well established for Abrikosov vortices in a bulk superconductor [1], but Josephson vortices in an SNS junction were only known to arrange as a one-dimensional chain [13,14,16]. Our key conceptual finding is that the 2D arrangement is hidden by angular averaging over the Fermi surface.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Two-dimensional vortex lattices are well established for Abrikosov vortices in a bulk superconductor [1], but Josephson vortices in an SNS junction were only known to arrange as a one-dimensional chain [13,14,16]. Our key conceptual finding is that the 2D arrangement is hidden by angular averaging over the Fermi surface.…”
Section: Discussionmentioning
confidence: 72%
“…It is known that the linear arrangement of the vortices along the superconducting interface is modified by insulating boundaries [9][10][11][12], in a junction of lateral width W comparable to the separation L of the interfaces. But in wide junctions (W L), when boundary effects are irrelevant, only linear arrangements of Josephson vortices are known [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with f 1 triplet generation being optimal for highly asymmetric ferromagnetic layer widths. 33 It is notable that the periodic occurrence of peaks in f 1 when varying D F 1 , evolves into a single maximum as h is reduced further.…”
Section: Triplet and Singlet Pair Correlationsmentioning
confidence: 99%
“…This behavior was qualitatively explained in terms of the longrange penetration of proximity-induced spin-1 triplet pairings due to the helical structure of the magnetization. 33 In practice however, simpler structures involving SF hybrids with uniform exchange fields are often preferable from both an experimental and theoretical perspective. 14,16,17,[24][25][26][27][28][29] Therefore, the primary aim of this work is the determination of experimentally optimal parameters for probing odd-frequency spin-1 triplet correlations with DOS signatures in nanoscale SF F spin valves.…”
Section: Introductionmentioning
confidence: 99%
“…Including all these ingredients makes it very challenging to obtain analytic insights, and usually one has to revert to numerics in order to produce quantitative or qualitative results. Numerical results based on a Keldysh-Usadel approach were used to study the supercurrent in diffusive junctions, with an asymmetric design or inhomogeneous exchange field [25,26]. There it was found that an anomalous supercurrent can also be caused by device asymmetries.…”
mentioning
confidence: 99%